BUSINESS DEVELOPMENT PLAN FOR SCALA WISHES PERFUME - Seli Rahayu Saputri; Meriza Hendri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The rapid growth of the fragrance industry, driven by increasing consumer awareness of lifestyle, personal identity, and self-branding, has created significant opportunities for local perfume brands in Indonesia. However, the market remains dominated by imported, mass-produced fragrances, while access to premium yet affordable local perfumes with strong emotional value and personalization is limited. Scala Wishes Perfume is a local brand that addresses this gap by offering high-quality extrait de parfum products with a distinctive character and competitive pricing. This study aims to develop a comprehensive business development plan for Scala Wishes Perfume by analyzing internal and external business environments, and the strategic aspects of marketing, operations, human resources, digitalization, innovation, risk management, legal compliance, and financial feasibility. Method: The research adopts a descriptive qualitative approach, using data collection techniques such as observation, interviews, document reviews, and secondary data analysis from industry reports and market research sources. Strategic analysis tools employed in this study include SWOT analysis, IFAS–EFAS, Porter’s Five Forces, Design Thinking, Business Model Canvas, Lean Canvas, and the Timmons Model. Financial feasibility is assessed using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Profitability Index, and Net Profit Margin.Result: The findings indicate that Scala Wishes Perfume has strong market potential supported by favorable industry growth trends and rising demand for premium local fragrances. Financial analysis confirms that the business development plan is economically viable, with positive NPV, a high IRR, a relatively short payback period, and a profitability index above one, indicating efficient capital utilization and attractive investment prospects. The study concludes that Scala Wishes Perfume has strong business potential and competitive advantages, particularly in product differentiation, emotional branding, and omnichannel marketing integration. With a well-focused strategy, effective resource management, and continuous innovation, Scala Wishes Perfume is expected to achieve sustainable growth and strengthen its position within Indonesia’s local perfume industry. Keywords: Business Planning, Cardiovascular Services, Healthcare Strategy, Hospital